Identification of the effect of lycopene on the inhibition of yellow fever-causing flavivirus by studying microarray gene expression data - Gholamreza Dadashi Oranj (Journal of Current Oncology and Medical Sciences, 2022)
Introduction: Yellow fever virus causes systemic disease of the liver, kidneys, myocardium and hemorrhage, which are high incidence and mortality. Lycopene is one of the effective antioxidants used to prevent the growth of cancerous tumors. DNAJC14 protein is a variant of heat shock protein (chaperone) Hsp40. Hsp40 chaperone protein (DNAJC14) that when overexpressed was able to mediate protection from yellow fever virus (YFV)-induced cell death. In this study, to find a new treatment for yellow fever, the effect of lycopene on the expression of DNAJC14 gene involved in yellow fever was investigated. Materials and methods: In this project, using bioinformatics software, such as Matlab and Cytoscape, the effect of lycopene on the expression of DNAJC14 gene, as well as the relationship of this gene with different genes have been investigated. Big gene expression data in the NCBI database were used for this study. Results: Analysis of microarray data showed that the expression level of DNAJC14 gene was increased under the influence of lycopene. Conclusion: The lycopene combination can be used as a preventative and even treatment for yellow fever viral disease due to the effect DNAJC14 gene expression.